The importance of ophthalmic signs in the diagnosis of suprasellar meningioma - A case report - Tan , A.K; P.S, Mallika; Aziz, S.; Asok, T.; G, Intan (Academy of Family Physicians of Malaysia, 2009)
A forty-two year old lady presented with gradual, painless, progressive blurring of vision of her left eye for four months. There were no other associated ocular or systemic complaints. Examination showed decreased visual acuity in both eyes and a pale optic disc on the left side. Visual field examination revealed a temporal field defect of the right eye which aroused the suspicion of an intracranial mass lesion. MRI of her brain revealed a suprasellar meningioma. We would like to emphasize the importance of visual field examination of both eyes in patients presenting with unilateral loss of vision.